A case of nevoid basal cell carcinoma syndrome associated with optic nerve coloboma and epiretinal membrane - Bin Meng; Min Cui; Ang Ji (BMC Ophthalmology)
Abstract Purpose To report the first case of nevoid basal cell carcinoma syndrome associated with optic nerve coloboma and epiretinal membrane in Chinese patient. Observations A 12-year-old female presented with bilateral visual decline. Examination revealed a porcelain-white optic nerve coloboma and epiretinal membrane in the right eye. OCT confirmed deepened optic disc excavation and a thin epiretinal membrane. Visual field testing showed an inferonasal arcuate scotoma. Systemic findings included odontogenic keratocyst and cutaneous basal cell carcinomas. Genetic testing identified a heterozygous PTCH1 mutation. Conclusions and importance Optic nerve coloboma and epiretinal membrane, though rare, can be initial signs of nevoid basal cell carcinoma syndrome. Ophthalmologists are critical in identifying these manifestations, enabling early diagnosis and comprehensive management.